A novel therapeutic agent, sodium oxybate, improves dystonic symptoms via reduced network-wide activity. Issue 1 (December 2018) - Simonyan, Kristina; Frucht, Steven; Blitzer, Andrew; Sichani, Azadeh; Rumbach, Anna
Abstract Oral medications for the treatment of dystonia are not established. Currently, symptoms of focal dystonia are managed with botulinum toxin injections into the affected muscles. However, the injection effects are short-lived and not beneficial for all patients. We recently reported significant clinical improvement of symptoms with novel investigational oral drug, sodium oxybate, in patients with the alcohol-responsive form of laryngeal focal dystonia. Understanding the mechanism of action of this promising oral agent holds a strong potential for the development of a scientific rationale for its use in dystonia. Therefore, to determine the neural markers of sodium oxybate effects, which may underlie dystonic symptom improvement, we examined brain activity during symptomatic speech production before and after drug intake in patients with laryngeal dystonia and compared to healthy subjects. We found that sodium oxybate significantly attenuated hyperfunctional activity of cerebellar, thalamic and primary/secondary sensorimotor cortical regions. Drug-induced symptom improvement was correlated with decreased-to-normal levels of activity in the right cerebellum. These findings suggest that sodium oxybate shows direct modulatory effects on disorder pathophysiology by acting upon abnormal neural activity within the dystonic network.